School Health Enterprise Management - Ramadan, Ramadan; Lubis, Ade Evriansyah; Eka Abdurrahman (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2023)
School Health Efforts are part of the substance of special service management engaged in school health. Special service management in schools is implemented to support learning and can meet the special needs of students in schools. This study aims to determine (1) the planning of School Health Effort at SDS Budi Mulia Medan, (2) the implementation of School Health Effort at SDS Budi Mulia Medan, (3) the control and implementation of School Health Effort at SDS Budi Mulia Medan, and (4) the factors that influence School Health Effort management at SDS Budi Mulia Medan. This research used a qualitative approach and case study research design. Data were collected through interviews, observation, and documentation techniques. To obtain data validity, researchers used source triangulation by finding different resource persons to find similar information. This study aims to describe the management of UKS at SDS Budi Mulia Medan.